2018
DOI: 10.5935/abc.20180116
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Iron Metabolism Changes in Patients with Acute Coronary Syndrome

Abstract: BackgroundIron metabolism disorders have been associated with an increased risk of cardiovascular events. However, the prognostic impact on patients (pts) with acute coronary syndrome (ACS) has yet to be clarified.ObjectiveTo determine the prognostic value of serum iron and ferritin levels in pts with ACS in the short and long-term.MethodsConsecutive pts admitted to a coronary care unit with a diagnosis of ACS, for a period of 2 years, were evaluated. The population was divided into tertiles of serum iron and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
(21 reference statements)
0
6
1
3
Order By: Relevance
“…The utility of serum iron itself for the assessment of iron status is limited because of diurnal variation in level, especially in nonfasting samples. 18 Duarte et al 19 showed that in patients admitted with ACS and in the lower tertile of serum iron level had a higher rate of mortality and HF at 1 year but not reinfarction. Likewise, Steen et al 20 failed to demonstrate an association between catalytic iron and risk of MI in 1,701 patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of serum iron itself for the assessment of iron status is limited because of diurnal variation in level, especially in nonfasting samples. 18 Duarte et al 19 showed that in patients admitted with ACS and in the lower tertile of serum iron level had a higher rate of mortality and HF at 1 year but not reinfarction. Likewise, Steen et al 20 failed to demonstrate an association between catalytic iron and risk of MI in 1,701 patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies even suggest a cytoprotective effect of ferritin, 22 whereas a prospective study in healthy Finnish men actually showed that elevated serum ferritin >200 mg/L was associated with a 2.2-fold greater risk of MI. 23 Duarte et al 19 showed that both low (<111) and high (>219) serum ferritin levels were associated with higher incidence of HF during hospitalization and mortality in patients with ACS. Moreover, a high serum ferritin level of 316 mg/L was an independent predictor of 1-year mortality.…”
Section: Discussionmentioning
confidence: 99%
“…O grau de anemia também é associado à severidade da insuficiência cardíaca, uma vez que a elevação do peptídeo natriurético atrial (BNP), a dilatação do ventrículo esquerdo, as disfunções nos processos de sístole e/ou diástole, o aumento progressivo da pressão na artéria pulmonar, e a redução do consumo de oxigênio durante esforço ou repouso estão correlacionados com a diminuição da qualidade de vida (Pereira et al,2012) Sabendo-se que o aumento nos níveis de citocinas, sendo diretamente envolvidas a IL6 e TNF alfa, tem ação não somente no estresse oxidativo, que provoca o extravasamento do BNP, como também na apoptose das células musculares, causando, assim, perda considerável e progressiva da massa esquelética (Duarte et al, 2018).…”
Section: Discussionunclassified
“…A anemia foi marcador independente de mau prognóstico na análise multivariada (mortalidade 47% vs 24,6%, p = 0,016, risco relativo 2,54). Duarte et al (2018) Níveis mais baixos e mais elevados de ferritina (1o e 3o tercil, respetivamente, ≤ 110; > 219 ng/ml) estiveram associados a uma maior ocorrência de IC em internamento e de morte a 1 ano. Um valor de ferritina> 316 ng/mL constituiu fator de risco independente de morte a 1 ano (OR ajustado 14 IC 95% 2,6-75,9).…”
Section: Cardosoet Al (2010)unclassified
See 1 more Smart Citation